Enhancement Of Physicochemical And Functional Properties Of Rice Flour Noodles Using Combined Hydroccolloids - Muhammad, Lubowa (2020)
Noodles are the main processed food product made from rice flour. However, fresh rice noodles have a weak structure, are generally fragile, sticky and easily collapse in overall structure upon high handling/temperature processing. They become soft, soggy and crumble into smaller pieces. This is a major compromise in sensory appeal. The objective of this study was to explore the use of various rice flour– hydrocolloid combinations for preparation of rice flour noodles with enhanced physicochemical and functional properties, which could enable them to withstand high handling and heat stresses without adverse effects on sensory properties